The Effect of Ownership Composition on Stock’s Liquidity: Evidence from Weak Corporate Governance Setting - Iskandrani, Majd; Al-Amareh, Asma’a (International Journal of Economics and Financial Issues, 2017)
This research seeks to investigate the relationship between ownership composition and stock’s liquidity in Jordan’s unique corporate setting. A multivariate regression was used to investigate the effect of ownership composition on stock’s liquidity for listed Jordanian firms during the period 2006-2014. The research finds that stock’s liquidity is higher for listed firms that are owned by government and foreign investors. Nevertheless, the complex pyramidal ownership structure could make corporate information less transparent and then increase the complexity of forecasting; hence, it results in less stock’s liquidity. Interestingly, the association between free float ownership and stock’s liquidity appears to be positive. The study investigates the effect of ownership structure mechanisms on the stock’s liquidity in an emerging market, and the findings provide some insight on how the stock’s liquidity might be affected by certain ownership and control features in the context of concentrated government ownership and complex pyramidal ownership structure. Keywords: Ownership, Composition, Stock’s Liquidity, Emerging markets. JEL Classifications: G10, G32